Doctor, tell me about ... a discussion of common drugs in medicine - Ismawi, Hidayatul Radziah (Hidayatul Radziah Ismawi, 2021)
This book aims to provide information on various common drugs in medicine for the public written in simple language by a qualified medical professional.